CULTURE DIALOGUE AND RESOCIALIZATION OF THE CONVICTED - Yu. V. Baranov (Russian Journal of Economics and Law, 2008)
It cannot be denied that Russia has rather specific conditions of development. One of the global specific features is the existence of borderline cultures, which is marked as culture dialogue in the international practice. Accordingly, any research should take this aspect into account, including the research in the sphere of resocialization of the Russian convicted for imprisonment and those exonerated from this punishment.